Peningkatan keterampilan membaca melalui implementasi media digital berbasis proyek pada siswa kelas V SDN Balerejo 02 - Afrilia Bayu Ivanka; Endang Sri Maruti; Vivi Rulviana (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to describe the implementation of project-based digital media through the use of flipbooks in Indonesian language learning, particularly speech texts, and to analyze its impact on improving students' reading skills. The study was conducted using a Classroom Action Research (CAR) approach in two cycles in fifth-grade students at SDN Balerejo 02, Madiun Regency. In Cycles I and II, learning was conducted using the Project-Based Learning (PjBL) model with the aid of flipbooks as digital media. Through project-based activities, students read and comprehend speech texts, then work on predetermined projects in groups. Data collection techniques used include observation, interviews, documentation, and assessment tests. Data analysis was carried out using qualitative and quantitative methods. Qualitative data were analyzed through observation and interviews, while quantitative data were analyzed by comparing student test results between cycle 1 and cycle 2. The results showed that in cycle 1, 53% of students achieved completion, while in cycle 2 it increased to 80%, with 100% completion in group assessment. This study shows that the implementation of project-based digital media through the use of flipbooks is effective in improving students' reading skills.